2023
DOI: 10.3389/fpubh.2023.1144674
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the participation of groups identified as underserved in cervical cancer screening in Europe: a scoping review of the literature

Abstract: BackgroundCervical cancer is a preventable and inequitably distributed disease. Screening plays a vital role in prevention, but many women face barriers to participation. The aims of this scoping review, undertaken to inform the co-design of interventions to equitably increase screening uptake, were to: (1) identify barriers and facilitators to cervical cancer screening for underserved populations, and (2) identify and describe the effectiveness of interventions aimed at improving participation in cervical can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
(240 reference statements)
0
4
0
Order By: Relevance
“…This is supported by an American study which found that high-risk and low-income groups have a much lower engagement in standard preventive healthcare services than other groups. 41 The systematic review conducted within the CBIG-SCREEN project 6 identified several reasons for vulnerable women’s low priority of preventive healthcare including childcare, work, pressure following substance abuse, complex migration processes and low self-esteem.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is supported by an American study which found that high-risk and low-income groups have a much lower engagement in standard preventive healthcare services than other groups. 41 The systematic review conducted within the CBIG-SCREEN project 6 identified several reasons for vulnerable women’s low priority of preventive healthcare including childcare, work, pressure following substance abuse, complex migration processes and low self-esteem.…”
Section: Discussionmentioning
confidence: 99%
“…Feelings of shame connected to CCS are a well-known barrier for women regardless of nationality and SES. The linked systematic review 6 found that embarrassment and fear of stigma were perceived as barriers to attendance in CCS for subgroups of vulnerable women in 18 of 33 articles. In a UK population-based survey, Waller et al 42 found that, in general, embarrassment was the most common barrier to attendance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPV testing, based on self-sampling, offers a possible response for disadvantaged women who are not reached by screening programmes. An ongoing study is working with such women in several countries in Europe to find solutions that meet their needs [ 47 ]. This can be as simple as finding a way that they can return samples when the postal system does not work.…”
Section: Main Textmentioning
confidence: 99%